Review: Rudolf Schmitt, Julia Schröder & Larissa Pfaller (2018). Systematische Metaphernanalyse. Eine Einführung [Systematic Metaphor Analysis. An Introduction] - Harloff, Raimund (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
With "Systematic Metaphor Analysis: An Introduction," Rudolf SCHMITT, Julia SCHRÖDER and Larissa PFALLER present a didactic reworking of systematic metaphor analysis. The authors first introduce the basic theoretical concepts of the method. Since every step is demonstrated by examples, this is always understandable even for newcomers to qualitative research. SCHMITT et al. then discuss common challenges and solution strategies in the research process, while highlighting the many possible applications of systematic metaphor analysis. The possibilities of presenting results with the aid of larger examples and different contexts for the use of systematic metaphor analysis are described. The authors conclude with a concise summary of the central theses. With its clear structure and its precise and intelligible language, the book more than lives up to the demands on an introduction to systematic metaphor analysis.